2013
DOI: 10.1371/journal.pone.0074799
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Targeting the hTAF4-TAFH Domain of TAF4 Represses Proliferation and Accelerates Chondrogenic Differentiation of Human Mesenchymal Stem Cells

Abstract: Transcription factor IID (TFIID) activity can be regulated by cellular signals to specifically alter transcription of particular subsets of genes. Alternative splicing of TFIID subunits is often the result of external stimulation of upstream signaling pathways. We studied tissue distribution and cellular expression of different splice variants of TFIID subunit TAF4 mRNA and biochemical properties of its isoforms in human mesenchymal stem cells (hMSCs) to reveal the role of different isoforms of TAF4 in the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 77 publications
0
40
0
Order By: Relevance
“…Alternative splice variants of TAF4 lack parts of the TAF homology domain, which mediates association with a variety of transcriptional factors. These TAF4 variants are differentially expressed in adult tissues, stem cells, and differentiated cells, potentially leading to different tissue-specific gene expression patterns 44 . To investigate how SETD6 regulates the expression of estrogen-responsive genes, we have performed chromatin immunoprecipitations of stably-expressed FLAG-SETD6 and transiently overexpressed FLAG-SETD6 in MCF7 cells, but failed to detect its presence at the promoter of CDKN1A , PGR , or TFF1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splice variants of TAF4 lack parts of the TAF homology domain, which mediates association with a variety of transcriptional factors. These TAF4 variants are differentially expressed in adult tissues, stem cells, and differentiated cells, potentially leading to different tissue-specific gene expression patterns 44 . To investigate how SETD6 regulates the expression of estrogen-responsive genes, we have performed chromatin immunoprecipitations of stably-expressed FLAG-SETD6 and transiently overexpressed FLAG-SETD6 in MCF7 cells, but failed to detect its presence at the promoter of CDKN1A , PGR , or TFF1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the AS mechanism underlying stem cell differentiation has piqued people's interest. Kazantseva et al (29) reported that depletion of hTAF4-TAFH domain from TAF4 isoforms caused enhanced chondrogenic differentiation of human MSCs (29). In addition, a novel alternative trasncript-quantitative polymerase chain reaction method was created by McAlinden et al (30) to quantify isoforms of alternatively spliced Col2a1 gene, and the results indicated that the majority of ATDC5 cells were the chondroprogenitor cells induced by the standard chondrogenic differentiation method.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the alternative splicing of TAF4 in various mouse and human cells and tissues identified multiple and complex splicing patterns [ 86 , 87 ]. In mouse, five alternative isoforms with deletions in the functional domains result in dominant negative effects in nuclear receptor-mediated transcriptional activation [ 86 ].…”
Section: Coordinated Switching Of Taf4 Alternatmentioning
confidence: 99%
“…In mouse, five alternative isoforms with deletions in the functional domains result in dominant negative effects in nuclear receptor-mediated transcriptional activation [ 86 ]. Complex patterns of TAF4 alternative splicing occur in different human tissues [ 87 ]. Although, a significant number of TAF4 alternatively spliced mRNAs contain a premature termination codon, indicating that these splice transcripts are subjected to the nonsense-mediated RNA decay, others preserve the open reading frame (ORF) and could be considered as possessing some functional properties in the cell.…”
Section: Coordinated Switching Of Taf4 Alternatmentioning
confidence: 99%